2010
DOI: 10.2337/db10-0021
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 Suppresses Src Activation and Reactive Oxygen Species Production in Diabetic Goto-Kakizaki Rat Islets in an Epac-Dependent Manner

Abstract: OBJECTIVEReactive oxygen species (ROS) is one of most important factors in impaired metabolism secretion coupling in pancreatic β-cells. We recently reported that elevated ROS production and impaired ATP production at high glucose in diabetic Goto-Kakizaki (GK) rat islets are effectively ameliorated by Src inhibition, suggesting that Src activity is upregulated. In the present study, we investigated whether the glucagon-like peptide-1 signal regulates Src activity and ameliorates endogenous ROS production and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
75
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 49 publications
3
75
2
Order By: Relevance
“…The mechanism for how exendin-4 mitigates ROS remains unknown. However, in line with our observations, a previous report indicated that exendin-4 decreases endogenous ROS production and increases ATP production in diabetic Goto Kakizaki rat islets through suppression of Src activation (26). It is reported that the reduced rate of mitochondrial respiration capacity contributes to impairment of mitochondrial function and cardiac function (5).…”
Section: Discussionsupporting
confidence: 81%
“…The mechanism for how exendin-4 mitigates ROS remains unknown. However, in line with our observations, a previous report indicated that exendin-4 decreases endogenous ROS production and increases ATP production in diabetic Goto Kakizaki rat islets through suppression of Src activation (26). It is reported that the reduced rate of mitochondrial respiration capacity contributes to impairment of mitochondrial function and cardiac function (5).…”
Section: Discussionsupporting
confidence: 81%
“…Among the two known mammalian EPAC isoforms, EPAC1 is ubiquitously expressed in all major tissues, whereas EPAC2 is mainly restricted to the brain, pancreas, and adrenal gland (1,2). Consistent with this tissue-specific expression pattern of EPAC isoforms, EPAC1 has been implicated in cardiac hypertrophy (3,4), fibrosis (5-7), and cancers (8-10), as well as leptin resistance (11), whereas EPAC2 is involved in diabetes/insulin secretion (12)(13)(14)(15)(16)(17)(18) and autism/depression (19)(20)(21).…”
mentioning
confidence: 75%
“…These results suggest that β‐cell function is actually well activated with combined use of sulfonylurea drugs and DPP‐4 inhibitors, although the effect of sitagliptin to lower glucagon 4 might also contribute to the reduced sulfonylurea doses. It is coming to be understood that incretin not only promotes the insulin release reaction in β‐cells 5,23 , but it also stimulates the insulin secretion response through multiple actions 24 , such as promoting adenosine triphosphate generation in mitochondria 25 , and both sulfonylurea and incretin act on exchange protein directly activated by cyclic adenosine monophosphate 2A in β‐cells 26,27 . Therefore, incretin and sulfonylurea are supposed to stimulate insulin secretion in coordinated and synergistic manners, and the present results appear to reflect these stimulatory effects of incretin and sulfonylureas on pancreatic β‐cells.…”
Section: Discussionmentioning
confidence: 99%